Propuesta de aplicación de un manual de procesos para el servicio de atención al cliente en Wapos bar restaurant. - Saldaña Roman, Erika Elizabeth (My University, 2018)
This written work presents a case study of WAPOS bar-restaurant, showing as a problem the ignorance of the adequate techniques for the management and correct development of their work, this leads to develop the activities in an empirical way, being able to establish processes that serve as orientation for achieve a quality service. The importance of offering a manual that allows an adequate control for the proper functioning of the company will help to carry out each activity stipulated in the document which will serve as a teaching tool for those who provide service, the project analyzes the problems that cause perform this research based on real data using as a support material a survey that allows analyzing and clarifying each aspect involved in customer service. In this document you will also find important concepts about the process manual and its service and customer service, design and preparation of each work area of the restaurant bar with their respective functions which will serve as help to improve their services. Through the organization chart of the place this document was elaborated establishing the division of the different departments when examining each detail, position and number of employees, allowing to raise the fulfillment of the established objectives oriented to improve and provide quality service.
Este trabajo escrito presenta un estudio de caso de WAPOS bar restaurante mostrando como problema el desconocimiento de las técnicas adecuadas para el manejo y desarrollo correcto de sus labores, esto conlleva a desarrollar las actividades de forma empírica, pudiendo establecer procesos que sirvan como orientación para alcanzar un servicio de calidad. La importancia de ofrecer un manual que permita llevar un control adecuado para el buen funcionamiento de la empresa ayudara a que se realice cada actividad estipulada en el documento lo cual servirá como instrumento de enseñanza para quienes prestan servicio, el proyecto analiza la problemática que motivo a realizar esta investigación basado en datos reales usando como material de apoyo una encuesta que permite analizar y aclarar cada aspecto involucrado en la atención al cliente. En este documento también se encontraran, conceptos importantes sobre manual de procesos y su servicio y atención al cliente, diseño y elaboración de cada área de trabajo del bar restaurante con sus respectivas funciones las cuales servirán como ayuda para mejorar sus servicios. Mediante el organigrama del lugar se elaboró este documento estableciendo la división de los diferentes departamentos al examinar cada detalle, cargo y número de empleados, permitiendo plantear el cumplimiento de los objetivos establecidos orientados a mejorar y brindar servicio de calidad.
Keywords: TÉCNICAS; RESTAURANTE; PRODUCTO; DOCUMENTO